Students’ Perceptions of the Advantages and Disadvantages of Using Artificial Intelligence in EFL Classrooms - Rahayu, Endang Mastuti; Irawan, Nico; Hertiki, Hertiki (Journal of English Teaching and Learning Issues, 2024)
This descriptive qualitative study examined the incorporation of Artificial Intelligence into EFL Classrooms, concentrating on its impact on thirty-fifth-semester students in a Research Methodology Course within an English Language Education Department. Data was collected through interviews and semi-structured questionnaires and analyzed using thematic analysis. The study indicated that the students predominantly possessed favorable attitudes toward AI in the educational process. They indicated that AI enhanced their language acquisition by delivering tailored feedback, presenting stimulating and interactive learning tasks, and allowing adaptable study options. Nonetheless, apprehensions were expressed regarding AI’s capability to supplant educators, monitor students’ development, and its accuracy and reliability. The study illustrated how AI might assist students with coming up with ideas, locating references, and improving the caliber of research projects. AI technologies could assist teachers in identifying and rectifying student errors, tracking progress, and accelerating the evaluation process, thereby conserving time during grading. These results highlight the significance of balancing AI use with human education to alleviate students' concerns. Future research may examine the efficacy of AI in assisting students with final projects, research proposals, publications, data analysis, and academic writing.